Labour pains: Content moderation challenges in Mastodon growth - Charlotte Spencer-Smith (Internet Policy Review, 2025)
After Elon Musk took over Twitter in October 2022, the number of users on the alternative social media platform Mastodon rose dramatically. The sudden influx of new users posed several challenges to content moderation distinct from those in large commercial social media. This article investigates the challenges Mastodon communities have faced and how their admins and content moderators have managed them. Based on scholarly literature, the article contextualises Mastodon as an open source, federated alternative to corporate social media and explains how content moderation is expected to occur in this model, including possible challenges from sudden growth in user numbers. The article then empirically investigates challenges experienced by Mastodon instances post-Musk, based on eight interviews with admins and moderators of seven instances and a representative of Independent Federated Trust & Safety (IFTAS), a non-profit organisation that supports Mastodon content moderators. The research finds that challenges and the responses to them vary depending on the characteristics of the instance, such as size, thematic focus and geography, andinstances tend to adopt measures tailored to their communities. However, a tension between centralisation and decentralisation, including Global North-South differences, cuts across the network, which may be accentuated by further growth.
Keywords: 300; Mastodon; Content moderation; Fediverse; Social media